PERFORMANCE OF FATTENING BUNAJI BULLS FED DIETS CONTAINING GRADED LEVEL OF PALM KERNEL CAKE - Sani, R. T.; Rekwot, G. Z.; Idowu, W.; Okin-Aminu, H. O. (FUDMA JOURNAL OF SCIENCES, 2021)
A fattening trial was conducted for 90 days using 20 Bunaji bulls with a live weight range of 190-200kg and aged 2-2.5 years to determine fattening performance. The bulls were fed diets containing varying levels of palm Kernel cake (PKC). Four bulls per treatment were allotted to 5 dietary treatments in Completely Randomised Design. Concentrate and basal diets of Digitaria smutsii were offered at 2% body weight. The data collected from the experiment were analysed using General Linear Model Procedure of SAS, (2002) The crude protein contents of the experimental diets varied between 15.63 and 20.31% while ME ranged from 11.75 to 11.78MJ/kg DM. The crude fibre varied from 13.92 to 23.31%. Average feed intake ranged between 8.67-9.11Kg/day with animals on 10, 20 and 40% PKC showed significant (P0.05) was observed in average weight gain for animals on diets containing 0 20 and 40% PKC inclusions. All the experimental bulls attained an average weight gain of between 1.13Kg to 1.33Kg. Cost per Kg gain was highest at 0% PKC inclusion and lowest at 40% PKC. Net benefit (NB) and value of weight gain (VWG) were significantly (P
Keywords: Bunaji bulls, Palm Kernel Cake, Partial budget, Weight gain